Fo Guang Shan’s Expansion in the Religious Market of Thailand: A SWOT Analysis - Su, Guiyu; Liu, Yaoping (Poligrafi, 2022)
As one of the prominent Mahayana Buddhist institutions from Taiwan, Fo Guang Shan (FGS) entered the religious market of Thailand as early as the 1990s. Its influence has grown tremendously among the local Chinese communities and Thai society. Despite this, there is a dearth of scholarship dedicated to FGS’s market expansion in Theravada-dominated Thailand. Through a SWOT analysis, this paper explores FGS’s marketing strategy for the Thai religious market. The findings suggest that FGS bears certain strengths, such as its appealing humanistic Buddhist doctrine, gift-giving networking skills and its strong emotional bonds with the Chinese communities in Thailand. These strengths have brought and will continuously provide FGS with opportunities for further expansion. However, FGS’s weakness is always there and obvious, given its foreign and non-mainstream nature and questionable legitimacy of existing as a Buddhist institution (or temple) in Thailand. All this has already caused threats to FGS’s missionary clergies and sanctuaries, mainly based in the Bangkok area, not to mention the growingly fierce competition from its Thai Theravada and local-born Mahayana counterparts.